Die poëtika van die liriek in die Afrikaanse literêre kabaret - Swart, Amanda (Afrikaans and Netherlandic Studies, 2017)
The growing interest in South African cabaret together with the unavailability of relevant information persuaded me that this part of South African theatre life and literature is a neglected phenomena. It needs urgent attention, not only for the literary importance, but also for the social relevance. Towards this end the assistance of Hennie Aucamp, who gave me access to his entire extensive cabaret collection, was of invaluable importance. Other information was collected in Europe in 1991. Cabaret performances in different countries were attended, libraries and museums visited and television programmes viewed, all in an attempt to experience at first hand and analyse the differences and similarities. One of the conclusions was that "cabaret", "music hall", "musical", "chanson", "revue", etcetera, have a lot in common, but are definitely not the same. Many people associate cabaret with almost naked girls with fish net tights. This idea was brought about by inter alia the film Cabaret, but is not what cabaret really is about. South African cabaret, especially our literary cabaret, is based on German "Kabarett". Literary cabaret works with literary conventions and is therefore important to South African literature and theatre. We are experiencing similar political and social changes to those in Europe during the fin-de-siècle. Cabaret in South Africa is growing because of these uncertainties. For example, the Dutch cabaret artist finds himself in a position where there is social welfare and political peace - and nothing is sacred anymore. It is very difficult for him then to make a statement in a climate where everything is allowed and possible. Germany is experiencing political uncertainties and cabaret is flourishing. This tendency can also be seen in other unstable countries, also in South Africa. This proves that, for cabaret to thrive, there must be specific political and social circumstances. Cabaret is the perfect way to remind us of our original reason for living: to love, to accept one another and to live in peace. While this is not possible, there will always be something to say and statements to make.